Purchasing power parity in Central and Eastern European countries. - Baharumshah, Ahmad Zubaidi; Borsic, Darja (Economics Bulletin, 2008)
This paper investigates the validity of the purchasing power parity (PPP) hypothesis for 13 Central and Eastern European countries (CEEC) in transition. The results based on the seemingly unrelated regression ADF (SURADF) method reveal that the PPP relationship holds in 7(6) out of the 13 countries when the real exchange rate is based on US dollar (euro). Our empirical findings appear to support a long-run PPP in some of the transition countries that appears insensitive to the base country.